COVID-19 vaccination mimicking lymph-node progression in a patient with melanoma: a case report. Issue 5 (October 2021) - Indini, Alice; Costa, Stefano; Ierardi, Anna Maria; Rijavec, Erika; Passoni, Emanuela; Grossi, Francesco
Abstract : COVID-19 vaccination has been rapidly implemented among patients with cancer. We present the case of a patient with high-risk resected cutaneous melanoma, who was a candidate for adjuvant treatment, with postsurgery 18-fluorodeoxyglucose (FDG) PET/computed tomography (CT) scan showing positive axillary lymph nodes after COVID-19 vaccination. This report presents a 50-year-old man with a history of stage IIA cutaneous melanoma. During follow-up, the patient experienced subcutaneous and lymph-node disease progression, documented with 18 FDG PET/CT scan. The patient underwent laparoscopic left para-aortic lymphadenectomy and excision of subcutaneous lesion. Histologic examination showed presence of melanoma metastases in 2 lymph nodes out of total 17 excised and neoplastic emboli to the subcutaneous tissue. In view of starting adjuvant nivolumab, the patient underwent CT scan restaging, with evidence of suspect centimetric periaortic and paracaval lymph nodes, which were deemed worthy of 18 FDG PET investigation. The 18 FDG PET/CT was negative for abdominal hypercaptation, but showed left axillary pathologic lymph nodes. The medical history of the patient revealed that he had received intramuscular Moderna COVID-19 mRNA vaccine in the left deltoid, one week before 18 FDG PET examination. Since the patient's clinical examination was negative and suspecting postvaccination false-positive adenopathy, bilateral axillary ultrasound was performed, excluding the presence of pathologic lymph nodes. The patient has started adjuvant treatment with nivolumab, which is currently ongoing. This case demonstrates unexpected findings in response to COVID-19 vaccination in a patient with melanoma. In this specific case, the detection of 18 FDG PET hypercaptation could significantly change the patient's management. With growing evidence about the pattern and occurrence of adenopathies after mRNA COVID-19 vaccination, recommendations for scheduling and interpretation of 18 FDG PET/CT scans among cancer patients will be implemented, in order to reduce equivocal findings and improve outcomes.